PENILAIAN KINERJA PELAYANAN BERBASIS SUMBER DAYA MANUSIA - Hariani, Dyah (Jurnal Ilmu Administrasi Negara, 2013)
This study aimsto determine the performance of services and the determinants of the services performance atRegional Water Company (PDAM) in Jepara Regency. The method used is a qualitative approach,and the data were collected by interview, observation and documentation. Analysis of the datausing the domain analysis techniques. The results showed that the performance of services atPDAM in Jepara are still low or less satisfactory. The deciding factor for poor performance ofservice, dominated by employees. The quantity of employee behaviours are less. Moreover, theirquality of the education level is not in accordance with the nature and type of positions assignedto the organization’s principal task at PDAM. Keywords: performance services, performance assesment, human resources, public service.